Digital Records Management and Administrative Effectiveness in Islamic Educational Institutions - Hermawan Primanda; Moh. Khusnuridlo; Gunawan Gunawan (Al-Qalam Institute, 2025)
Digital transformation has encouraged higher education institutions to strengthen digital records management as an essential component of institutional governance and administrative effectiveness. This study aims to examine how digital records management contributes to administrative effectiveness at Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember through institutional governance, information accessibility, and administrative workflow. A qualitative case study design was employed. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving university administrators, heads of administrative units, archive management personnel, information technology staff, and academic administrative officers. The data were analyzed using Braun and Clarke's thematic analysis, supported by triangulation, member checking, peer debriefing, and an audit trail to ensure the trustworthiness of the findings. The results reveal that digital records management has been institutionalized through organizational policies, standardized operating procedures, integrated information systems, data security mechanisms, and role-based access control. Its implementation improves information accessibility, streamlines administrative workflow, strengthens inter-unit coordination, and enhances administrative efficiency, service quality, institutional accountability, evidence-based managerial decision-making, and organizational memory. The study concludes that digital records management constitutes a strategic organizational capability integrating governance, information management, and institutional learning to strengthen administrative effectiveness and promote sustainable higher education governance. These findings further demonstrate that digital records management extends beyond archival functions by creating strategic organizational value for institutional governance and evidence-based decision-making.